(untitled) (Revista Espinhaço, 2025)
In the Jequitinhonha Valley (MG), popular culture is rich and diverse. Small farmers gather at the Araçuaí market to sell their products. Among them, the women of the “Farmacinha Lagoão” display their medicinal plants and clays, to be used as exfoliants, cell regenerators, moisturizers, skin and hair lighteners and antiseptics. What secrets do these clays hold? Based on the hypothesis that the possible cosmetic effects of these clays are due to attributes related to their colors, the objective of this work was to evaluate the granulometric, chemical, mineralogical and geochemical composition of blue, white, black, pink, green and red clays. The granulometry and mineralogy of the clays were determined, respectively, by laser diffraction and X-ray diffractometry. The mineralogical description, routine chemical and geochemical analyses were performed respectively by microscopy, X-ray fluorescence and elemental analysis. In all clays, the silt fraction predominates, except for green clay, where the sand fraction predominates. The clays with the highest colloid content are white and pink. All clays have high levels of Si and Al, but Fe is present in pink and red clays, C is significant in black clay, and K is high in blue and green clays. All clays contain quartz and kaolinite, and white, black, pink, and green clays contain illite. The clays present distinct granulometric, geochemical, and mineralogical compositions, which are related to their different cosmetic uses.